Development and validation of a nomogram for predicting 28-day mortality in critically ill patients with acute gastrointestinal injury: prospective observational study - Wang, Youquan; Li, Yanhua; Zhang, Yuhan; Wang, Huimei; Li, Yuting; Zhang, Liying; Zhang, Chaoyang; Gao, Meng; Li, Hongxiang; Zhang, Dong (Frontiers in Nutrition, 2024)
Objective: Developing and validating a clinical prediction nomogram of 28-day mortality in critically ill patients with acute gastrointestinal injury (AGI).Methods: Firstly, the construction of a clinical prediction model was developed using data obtained from a prospective observational study from May 2023 to April 2024.Then, data from a prospective multicenter observational study conducted in the intensive care units of 12 teaching hospitals in 2014 were utilized to independently and externally validate the clinical prediction model developed in the first part. We first screened the covariates of the development cohort by univariate cox regression, and then carried out cox regression analysis on the development cohort by backward stepwise regression to determine the optimal fitting model. Subsequently, a nomogram was derived from this model.A total of 1102 and 379 patients, 28-day mortality occurred in 20.3% and 15.8% of patients respectively, were included in the development and validation cohort, respectively. We developed a nomogram in critically ill patients with AGI and the AGI grade, APACHE II score, Mechanical ventilation (MV), Feeding intolerance (FI) and daily calorie intake (DCI) in 72 h, were independent predictors of 28-day mortality, with the OR of the AGI grade was 1.910 (95% CI, 1.588 -2.298; P < 0.001), the OR of APACHE II score was 1.099 (95% CI, 1.069 -1.130; P < 0.001), the OR of MV was 1.880 (95% CI, 1.215 -2.911; P = 0.005), the OR of FI was 3.453 (95% CI, 2.414 -4.939; P < 0.001) and the DCI > 0.7 or < 0.5 of calorie target is associated with increased 28-day mortality, with OR of 1.566 (95% CI, 1.024 -2.395; P = 0.039) and 1.769 (95% CI, 1.170 -2.674; P = 0.007), respectively. Independent external validation of the prediction model was performed. This model has good discrimination and calibration. The DCA and CIC also validated the good clinical utility of the nomogramThe prediction of 28-day mortality can be conveniently facilitated by the nomogram that integrates AGI grade, APACHE II score, MV, FI and DCI in 72 h in critically ill patients with AGI.